Design of an integral sliding mode controller for reducing CO2 emissions in the transport sector to control global warming - Abid Mehmood; Mohsan Hassan; Pita Donald; Mohammed M. A. Almazah (Scientific Reports)
Abstract Carbon dioxide (CO2) is the significant contributor to greenhouse gases and plays a crucial role in the greenhouse effect and climate change. The primary source of CO2 emissions is fossil fuel combustion, basically due to human activities and transportation activities. The objective of this research is to develop a dynamic model aimed at mitigating global warming by reducing atmospheric CO2 emissions resulting from the transportation sector. The model includes equations for atmospheric CO2 emissions, human population, vehicle population, and global warming. Initially, the stability of the model at each equilibrium point is determined by analyzing the eigenvalues of the Jacobian matrix. Subsequently, sensitivity analysis is performed to predict the impact of any parameter of a vehicle population and CO2 emissions causing global warming. The vehicle parameters are then optimized by applying an integral sliding mode controller (ISMC) to decrease CO2 emissions and minimize global warming. The ISMC method effectively reduces CO2 emissions and offers stability for human and vehicle populations, ultimately leading to a reduction in global warming. It is has been found that reducing the vehicle population by 20% can lead to about 4% reduction in CO2 emissions. This study integrates optimization control techniques to develop a comprehensive model to address CO2 emissions and global warming, providing a robust framework for sustainable environmental management.